The role of genetic and epigenetic modifications as potential biomarkers in the diagnosis and prognosis of thyroid cancer - Sabi, Essa M. (Frontiers in Oncology, 2024)
Thyroid cancer (TC) is the most common endocrine cancer, which contributes to more than 43,600 deaths and 586,000 cases worldwide every year. Among the TC types, PTC and FTC comprise 90% of all TCs. Genetic modifications in genes are responsible for encoding proteins of mitogen-associated protein kinase cascade, which is closely related with numerous cellular mechanisms, including controlling programmed cell death, differentiation, proliferation, gene expression, as well as in genes encoding the PI3K (phosphatidylinositol 3-kinase)/protein kinase B (AKT) cascade, which has contribution in controlling cell motility, adhesion, survival, and glucose metabolism, have been associated with the TC pathogenesis. Various genetic modifications including BRAF mutations, RAS mutations, RET mutations, paired-box gene 8/peroxisome proliferator-activated receptor-gamma fusion oncogene, RET/PTC rearrangements, telomerase reverse transcriptase mutations, neurotrophic tyrosine receptor kinase fusion genes, TP53 mutations, and eukaryotic translation initiation factor 1A X-linked mutations can effectively serve as potential biomarkers in both diagnosis and prognosis of TC. On the other hand, epigenetic modifications can lead to aberrant functions or suppression of a range of signalling cascades, which can ultimately result in cancer. Various studies have observed the link between epigenetic modification and multiple cancers including TC. It has been reported that several epigenetic alterations including histone modifications, aberrant DNA methylation, and epigenetic modulations of non-coding RNAs can play significant roles as potential biomarkers in the diagnosis and prognosis of TC. Therefore, a good understanding regarding the genetic and epigenetic modifications is not only essential for the diagnosis and prognosis of TC, but also for the development of novel therapeutics. In this review, most of the major TC-related genetic and epigenetic modifications and their potential as biomarkers for TC diagnosis and prognosis have been extensively discussed.